2020
DOI: 10.1177/2158244019899701
|View full text |Cite
|
Sign up to set email alerts
|

Dilemma of Natural Resource Abundance: A Case Study of Kuwait

Abstract: There is a lively debate about the relationship between a nation’s natural resource abundance and economic growth. Some view natural resource abundance as a curse, whereas others view it as a blessing. This study examines the economic, social, and political effects of resource abundance in an oil-rich country, Kuwait, using data from 1984 to 2014. This study analyzes the short- and long-run impacts of resource rents on per capita gross domestic product (GDP), productivity, human capital, and institutional qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 208 publications
(330 reference statements)
1
13
0
Order By: Relevance
“…To capture the influence of differences in factor endowment (FEDW) on global value chain participation, we introduce two different proxies; total labour force (lab) and total natural resource rents (Tnrr) in line with Weng (2010) and Ruba and Andrew (2020) respectively. We expect a positive influence of FEDW on GVCP.…”
Section: 0: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To capture the influence of differences in factor endowment (FEDW) on global value chain participation, we introduce two different proxies; total labour force (lab) and total natural resource rents (Tnrr) in line with Weng (2010) and Ruba and Andrew (2020) respectively. We expect a positive influence of FEDW on GVCP.…”
Section: 0: Methodsmentioning
confidence: 99%
“…In addition to institution, several studies have also demonstrated that factor endowment is crucial for value chain participation. The endowment view argued that differences in natural resource endowment had an indirect significant influence on intra-regional trade through its impact on the quality of institutions (Mohsen, 2017;Ruba and Andrew, 2020) and directly on the global value chain (Barnabas et al, 2019). Mathias, Axel, Silke and Steffen ( 2007)'s empirical study on the nexus between institutions, governance, and trade in ECOWAS countries revealed that population, a proxy for factor endowment has an insignificant positive impact on intra-regional trade throughout the estimations.…”
Section: 0: Review Of Literaturementioning
confidence: 99%
“…Following Aljarallah and Angus (2020), we begin the development of our analytical framework by explaining the Solow (1956) model. This model is a simplification of the analysis of the determinants of economic growth.…”
Section: Analytical Frameworkmentioning
confidence: 99%
“…There is debate about the relationship between a country's natural resource abundance and economic growth. Case study [14] looks at the impact of resource surpluses in Kuwait using data from 1984 to 2014. Resource exports are relatively important in resource-rich countries, as they can be a major source of economic growth and development.…”
Section: Institutionsmentioning
confidence: 99%
“…R. Aljaralla and E. Angus analyze the impact of resource rent on GDP, labor productivity, human capital and the quality of institutions. Their research shows that using the Distributed Lag Autoregressive Model (ADL) and Error Correction Model (ECM), resource rent increases GDP per capita only in the short term; however, resource rent degrades productivity, human capital, and the quality of institutions both in the short and long term [14]. See [21,43,47].…”
Section: Institutionsmentioning
confidence: 99%